The Use Dexmedetomidine as a Total Intravenous Anesthesia–Propofol Adjuvant for Aneurysm Clipping - Sepriwan, Tori; Saleh, Siti Chasnak; Lalenoh, Diana Ch. (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2026)
Intracranial aneurysm is a cerebrovascular disease with a high mortality rate, particularly in cases of rupture. Aneurysm clipping surgery is one of the definitive management methods; however, it involves significant hemodynamic fluctuations that may lead to intraoperative complications and worsen prognosis. Hemodynamic stability and rapid anesthetic recovery are crucial aspects for the success of this procedure. We report a case of a 57-year-old female with a saccular aneurysm in the right M1 segment of the middle cerebral artery, scheduled for aneurysm clipping surgery. The patient had previously undergone decompressive craniectomy and hematoma evacuation due to non-traumatic intracranial hemorrhage, which was not initially diagnosed as an aneurysm, and showed no significant improvement postoperatively. In anesthetic management, dexmedetomidine was used as an adjuvant to maintain hemodynamic stability and support rapid recovery. Throughout the procedure with TIVA- Propofol, dexmedetomidine effectively maintained stable blood pressure without episodes of hypertension, hypotension, or bradycardia. The patient did not experience significant intraoperative complications, and postoperative recovery was optimal. This emphasizes the critical role of dexmedetomidine within modern anesthetic approaches to the management of intracranial aneurysm cases.